Nilai Ekonomi Limbah Mainan Plastik - Budiana Budiana; Ades Sugita; Achmad Nurcholis; Annisa Wibawanthi; Nurul Fauziah; Rumina nFn (Ecopreneur : Journal of Sharia Economics Study Program, 2020)
The problem of garbage is a problem that is a very important issue every day, this results in the accumulation of garbage along the road and the environment. Waste must begin to be thought about processing and recycling. The community or the private sector is finally able to create business opportunities for waste recycling. Not only to clean waste but as a small business that is able to absorb new workers. Processing plastic toy waste in addition to opening promising business opportunities but also providing opportunities for other communities. Communities without capital are looking for from house to house to workers who are in processing. Therefore, researchers conducted a literature study, interviews, observations and documents about the processing of plastic waste up to the sales turnover of plastic toy waste. In scientific papers the writing method used is descriptive qualitative in the form of case studies, by describing the results of interviews, observations, and sales documents. Based on the results of previous studies the authors can conclude that plastic waste has economic value. The method used is to form a direct visit or direct observation to get data. The data collected was then corroborated by interviews with the owners of the plastic toy waste treatment. From these observations, plastic toy waste has economic value with an average monthly turnover of Rp. 400,000,000. This research is certainly expected as new knowledge about the plastic waste business as a business opportunity. Keywords: Economic Value; Waste; Plastic Toys Abstrak Masalah sampah merupakan masalah yang setiap hari menjadi masalah yang sangat penting, hal ini mengakibatkan penumpukkan sampah di sepanjang jalan dan lingkungan.Sampah harus mulai dipikirkan tentang pengolahan dan pendaurulangannya. Masyarakat atau pihak swasta akhirnya mempu menciptakan peluang-peluang usaha pendaurulangan limbah sampah. Bukan hanya untuk membersihkan limbah sampah tapi sebagai usaha kecil yang mampu menyerap tenaga kerja baru. Pengolahan limbah plastik mainan selain membuka peluang usaha yang menjanjikan tapi juga member peluang untuk masyarakat lainnya.Masyarakat tanpa modal yang mencari dari rumah kerumah sampai para pekerja yang berada di pengolahan.Oleh karenanya, peneliti melakukan studi literature, wawancara,observasi serta dokumen tentang proses pengolahan limbah plastik sampai dengan omzet penjualan dari limbah plastik mainan tersebut. Dalam karya tulis ilmiah metode penulisan yang digunakan adalah kualitatif-deskriptif dalam bentuk studi kasus, dengan cara mendeskripsikan hasil dari wawancara, observasi, dan dokumen hasil penjualan. Berdasarkan hasil penelitian sebelumnya penulis dapat menyimpulkan limbah plastik memiliki nilai ekonomi.Cara yang digunakan dengan membentuk mendatangi secara langsung atau observasi langsung utnuk mendapatkan data. Data yang terkumpul lalu diperkuat dengan wawancara dengan pemilik pengolahan limbah plastic mainan tersebut. Dari hasil observasi tersebut limbah plastik mainan memiliki nilai ekonomi dengan omzet perbulan rata-rata adalah Rp 400.000.000. Penelitian ini tentunya diharapkan sebagai pengetahuan baru tentang usaha limbah plastic sebagai peluang usaha. Kata kunci: Nilai Ekonomi; Limbah; Mainan Plastik